2015
DOI: 10.1016/j.molonc.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Altered purinergic receptor‐Ca2+ signaling associated with hypoxia‐induced epithelial‐mesenchymal transition in breast cancer cells

Abstract: Hypoxia is a feature of the microenvironment of many cancers and can trigger epithelial-mesenchymal transition (EMT), a process by which cells acquire a more invasive phenotype with enriched survival. A remodeling of adenosine 5'-triphosphate (ATP)-induced Ca(2+) signaling via purinergic receptors is associated with epidermal growth factor (EGF)-induced EMT in MDA-MB-468 breast cancer cells. Here, we assessed ATP-mediated Ca(2+) signaling in a model of hypoxia-induced EMT in MDA-MB-468 cells. Like EGF, hypoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 59 publications
2
59
1
Order By: Relevance
“…These observations supported the idea that high expression of the P2Y6 receptor mediated EMT induction and correlated with the high invasivity of breast cancer tumors. In agreement with the in vitro evidence, patients with tumors showing high P2Y6 receptor expression have a poor prognosis [92,101]. Importantly, it was shown that UDP is released in response to chemotherapy, highlighting a putative mechanism for drug resistance [101].…”
Section: Adora2asupporting
confidence: 78%
See 2 more Smart Citations
“…These observations supported the idea that high expression of the P2Y6 receptor mediated EMT induction and correlated with the high invasivity of breast cancer tumors. In agreement with the in vitro evidence, patients with tumors showing high P2Y6 receptor expression have a poor prognosis [92,101]. Importantly, it was shown that UDP is released in response to chemotherapy, highlighting a putative mechanism for drug resistance [101].…”
Section: Adora2asupporting
confidence: 78%
“…ATP elicited a reduced Ca 2+ response during EMT in MDA-MB-468 breast carcinoma cells under hypoxic conditions; this response correlated with a lower expression of P2X4, P2X5, P2X7, P2Y1, and P2Y11 purinergic receptors, and an elevated expression of P2Y6 [92]. P2Y6 receptor overexpression has been associated with EMT induced by growth factors and hypoxia; accordingly, the pharmacological inhibition or genetic silencing of this receptor prevented the induction of EMT and the increase in cellular migration [92,101].…”
Section: Adora2amentioning
confidence: 90%
See 1 more Smart Citation
“…This has been a huge problem in the studies reported so far. To our knowledge, only five articles have been published that investigate P2RY11 mRNA expression without detecting the fusion transcript [17][18][19][20][21]. All other studies have featured primer sets predicted additionally to recognize the fusion transcript (Table S1).…”
Section: P2ry11 or Ppan-p2ry11?mentioning
confidence: 99%
“…The MDA-MB-468 breast cancer cell line is a commonly utilized in vitro model for the study of EMT in the context of defining responses to signals from the surrounding tumor microenvironment [11,19,20]. TPC2 but not TPC1 silencing significantly inhibited EGFinduced vimentin expression relative to siNT in MDA-MB-468 cells (Fig.…”
Section: Tpc2 Silencing Attenuates Egf-induced Vimentin Expression Inmentioning
confidence: 99%